Pengaruh Leverage, Opinion Shopping, Prior Opinion, Dan Audit Quality Terhadap Opini Audit Going Concern: Studi Empiris pada Perusahaan Infrastruktur yang terdaftar di BEI tahun 2018-2023 - Perdana, Qory Putri; Afriyenti, Mayar (Universitas Negeri Padang, 2026)
This study aims to prove the influence of leverage, opinion shopping, prior opinion, and audit quality on going concern audit opinions in infrastructure companies listed on the Indonesia Stock Exchange. This study uses 25 companies as a sample. The sampling technique used in this study is purposive sampling. The data analysis method of this study is logistic regression analysis using SPSS. It was found that leverage, opinion shopping, and audit quality had no effect on the going concern audit opinion, while the prior opinion had an effect on the going concern audit opinion. For further research on the going concern audit opinion, it is expected to use other variables that have not been researched in this study. The next researcher is also expected to be able to use companies in other sectors in conducting research on audit opinions going concern and it is hoped that the research year will also be added and the latest.